Extracellular Ca2+ Selectively Enhances Adriamycin-induced Cell Death in Human Hepatoma Cells - Huang, Xuexue; Xu, Yuan; Liu, Yanyi; Xie, Hong; Wang, Jiachun; Wu, Zhigang (Current Cancer Drug Targets, 2015)
It has been shown that the regulatory mechanisms of Ca2+ signaling between tumor and normal cells are different, providing new insight into the pharmacological modulation of anticancer drugs. However, it remains unclear whether there is any difference between hepatoma and normal hepatic cells in their response to extracellular Ca2+ ([Ca2+]e). In the present study, the growth inhibition, apoptosis and necrosis rates of human normal embryo hepatic L02 and human hepatoma HepG2 cells exposed to additional calcium ([Ca2+]a)and adriamycin (ADM), a chemotherapeutic agent to treat hepatocellular carcinoma, were measured by MTT and annexin V/PI assays, respectively. The results showed that the growth inhibition, necrosis and apoptosis rates, as well as intracellular Ca2+ concentrations ([Ca2+]i) induced by [Ca2+]e in HepG2 cells were higher than those in L02 cells. Moreover, [Ca2+]e was able to selectively enhance ADM-induced growth inhibition, apoptosis and necrosis in HepG2 cells, but not in L02 cells. ADM and [Ca2+]a co-treatment had a significant interaction effect to increase [Ca2+]i in both cell lines, although there was no significant difference in [Ca2+]i between the two cells. To further elucidate the mechanisms involved in the selective promotion of [Ca2+]e in HepG2 and L02 cells, the levels of these apoptosis regulatory proteins (bcl-2, bax and procaspase-3) and the caspase-3 activity following treatment of HepG2 and L02 cells with ADM or/and [Ca2+]a were investigated. The results showed that treating HepG2 cells with [Ca2+]a and ADM increased the level of bax protein and caspase-3 activity while decreasing the level of bcl-2 protein, compared with treatment with ADM alone. However, no significant change was noted in L02 cells. These results indicate that hepatoma HepG2 cells are more sensitive to [Ca2+]e than normal hepatic L02 cells and that [Ca2+]a can selectively enhance ADMinduced cell death in HepG2 cells. The mechanism of this intensive pro-apoptotic effect can be ascribed to up-regulation of bax and the simultaneous down-regulation of bcl-2, followed by the switch from procaspase-3 to caspase-3, which executed apoptosis. The present data suggest the potency of the calcium ion as an enhancer of ADM.
Keywords: Bax